Preoperative sonographic features of follicular thyroid carcinoma predict biological behavior: A retrospective study - Lai, Xingjian (Medicine (Baltimore), 2018)
Little is known regarding biological behavior of follicular thyroid carcinomas (FTCs) according to ultrasonography features. We investigated whether there was a difference in biological behavior between benign-looking FTCs (B-FTCs) and malignant-looking FTCs (M-FTCs). A total of 55 cases of FTC between January 2000 and December 2015 were included. B-FTCs were defined as showing none of the accepted ultrasonography criteria for malignancy, and M-FTCs were defined as showing at least one of the accepted ultrasonography criteria for malignancy. Clinicopathologic factors and sonographic features were compared between B-FTCs and M-FTCs. Based on the degree of invasiveness, FTCs were divided into minimally invasive FTCs (MI-FTCs) and widely invasive FTCs (WI-FTCs) on pathology. Sonographic features were compared between MI-FTCs and WI-FTCs. Compared with the patients with B-FTCs (31/55, 56.4%), the patients with M-FTCs showed a significantly higher prevalence of WI-FTCs, central lymph node metastases, lateral lymph node metastases as well as extrathyroidal extension (P < .001, P = .012, P = .031, and P = .032, respectively). M-FTCs with more than one malignancy features on ultrasonography showed a significantly higher prevalence of extrathyroidal extension than M-FTCs with only one ultrasonography malignancy feature (P = .022). Compared with MI-FTCs (41/55, 74.5%), an irregular shape, a spiculated/microlobulated boundary, no peripheral halo ring, hypoechogenicity and microcalcification were more frequent in WI-FTCs (P < .001, P = .003, P = .002, P = .015, and P = .016, respectively). Our results demonstrated that B-FTCs had better prognostic indicators than M-FTCs. Therefore, preoperative US features can serve as a useful tool for predicting biological behavior in FTC.